Perancangan sistem informasi manajemen pendaftaran online vaksinasi covid-19 berbasis website di UPT layanan kesehatan institut teknologi Bandung - Warliyah, Lilis; Karyadi, Karyadi; Suwartika, Rini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Initially, the registration process for the Covid-19 vaccination still used a manual system which resulted in long queues, data redundancies, identity input errors, schedule rescheduling, and an increase in the registrant quota. The purpose of this study was to design a website-based online registration information system so that it can be accessed anywhere by inputting the data of vaccination participants independently so that the data obtained is more accurate and stored in a computerized manner and makes it easier for administrative staff to re-register. Is a qualitative method based on objective aspects in identifying problems in order to find solutions and implement them in a system design. Data collection techniques using interviews, observation, documentation, and literature study. While the system method uses the waterfall System Development Life Cycle (SDLC) which is a classic sequential life cycle starting from analysis, design, coding, testing, and support stages. With an online vaccination registration information system, it can increase effectiveness and efficiency and produce the expected output.